Leishmania infection in a population of dogs: an epidemiological investigation relating to visceral leishmaniasis control - Penaforte,Klauber Menezes (2013)
Identification of factors associated with Leishmania infection in dogs is essential for targeting visceral leishmaniasis control actions. Thus, the present study analyzed some of these factors in a population of dogs in a Brazilian municipality, along with the limitations of control strategies implemented there. The association between the exposure variables and occurrences of infection was analyzed through logistic regression models. The disease control interventions were treated qualitatively. Out of the 755 animals examined, 13.6% (103/755) were seropositive. Of these, 23.3% (24/103) were asymptomatic and 76.7% (79/103) presented at least one clinical sign possibly associated with visceral leishmaniasis. With weak associations, purebred, shorthaired, over 5 years of age, male and large dogs were more prone to infection. The latter two variables formed the final regression model and the association with dog size was statistically significant. The control strategies developed presented limitations and a great number of seronegative dogs was culled. The data presented contribute towards better understanding of the dynamics of infection in canine visceral leishmaniasis and indicate that actions aimed towards adequate implementation of Visceral Leishmaniasis control program in Brazilian endemic areas should be prioritized.